Pengaruh Social Media Marketing terhadap Customer Engagement dengan Loyalitas Merek dan Kepercayaan sebagai Variabel Mediasi - Rachmadhaniyati Rachmadhaniyati; Sanaji Sanaji (Jurnal Ilmu Manajemen, 2021)
The rapid development of technology has an impact that can be seen from changes in people's lifestyles. Some marketers take advantage of this technological development by marketing their products through social media. For this reason, marketers must also be able to adjust marketing channels through social media so that users can access them easily. Marketing tools through social media are the marketplace, Facebook, Twitter, Instagram, and others. This study aims to determine the effect of social media marketing on customer engagement with brand loyalty and trust as mediating variables on online shop actors. This study uses 200 samples collected through an online questionnaire with a purposive sampling technique with criteria of at least 16 years of age, active social media users, and having shopped online. We used the Partial Least Square (PLS) method to test the hypothesis. The results of this study indicate that social media marketing affects customer engagement. This study also proves that brand loyalty and trust have a significant relationship with social media marketing. However, it was found that trust did not affect customer engagement. That is, trust is not able to strengthen the influence of social media marketing on customer engagement.